Math, asked by ektarai5712, 1 year ago

Find the five term:– a=13 , d=–12

Answers

Answered by amitkumar44481
3

AnsWer :

→ 13 , 1 , - 11 , - 23 , - 35

SolutioN :

We have ,

  • a = 13.
  • d = - 12.

Let,

  • " a " first term.
  • " d " common difference.

We know, General Formula of AP

→ a , a + d , a + 2d , a + 3d .....

Now,Putting given.

→ 13 , 13 + ( -12 ) , 13 + 2( - 12 ) , 13 + 3( -12 ) + 13 + 4( -12 )

→ 13 , 1 , - 11 , - 23 , - 35 .

Our AP become ( 13 , 1 , - 11 , - 23 , - 35 )

Verification :

  • a1 = 13.
  • a2 = 1.
  • a3 = - 11.
  • a4 = - 23.
  • a5 = - 35.
  • a6 = - 47.

† an = a + ( n - 1 )d.

So,

  • a1 = a → 13.
  • a2 = a + d → 13 - 12 = 1.
  • a3 = a + 2d → 13 + 2( - 12 ) = - 11.
  • a4 = a + 3d → 13 + 3( -12 ) = - 23.
  • a5 = a + 4d → 13 + 4( - 12 ) = - 35.
Answered by BrainlyPopularman
1

Question :

Find first five term of A.P. , if a = 13 and d = -12

ANSWER :

• First five term are 13 , 1 , -11 , -23 , -35

EXPLANATION :

GIVEN :

First term of A.P. (a) = 13

• Common difference of A.P. (d) = -12

TO FIND :

• First five term of A.P.

SOLUTION :

We know that nth term of A.P. is –

 \\ \implies \large{ \red{ \boxed{ \bold{ T_{n} = a + (n - 1)d }}}}  \\

• So that –

 \\  \:  \: \longrightarrow \:  \: { \bold{First \:  \:  term( T_{1}) = a + (1 - 1)d }}  \\

 \\  \:  \: \: \: \: \: \: \: \: { \huge{.}} \:  \: { \bold{First \:  \:  term( T_{1}) = a   = 13 }}  \\

 \\  \:  \: \longrightarrow \:  \: { \bold{Second  \:  \:  term( T_{2}) = a + (2 - 1)d }}  \\

 \\  \:  \:   \: \: \: \: \: \: \:  { \huge{.}} \:  \: { \bold{Second \:  \:  term( T_{2}) = a  + d  }}  \\

 \\  \:  \:  \: \: \: \: \: \: \:  { \huge{.}} \:  \: { \bold{Second \:  \:  term( T_{2}) = 13   - 12  = 1  }}  \\

 \\  \:  \longrightarrow \:  \: { \bold{Third  \:  \:  term( T_{3}) = a + (3 - 1)d }}  \\

 \\  \:  \:  \: \: \: \: \: \: \:  { \huge{.}} \:  \: { \bold{Third \:  \:  term( T_{3}) = a  + 2d  = 13  +2 ( - 12) }}  \\

 \\  \:  \:  \: \: \: \: \: \: \:  { \huge{.}} \:  \: { \bold{Third \:  \:  term( T_{3}) =  - 11 }}  \\

 \\  \:  \longrightarrow \:  \: { \bold{Fourth  \:  \:  term( T_{4}) = a + (4 - 1)d }}  \\

 \\  \:  \:  \: \: \: \: \: \: \:  { \huge{.}} \:  \: { \bold{Fourth \:  \:  term( T_{4}) = a  + 3d  = 13  +3 ( - 12) }}  \\

 \\  \:  \:  \: \: \: \: \: \: \:  { \huge{.}} \:  \: { \bold{Fourth \:  \:  term( T_{4}) =  - 23 }}  \\

 \\  \:  \longrightarrow \:  \: { \bold{Fifth  \:  \:  term( T_{5}) = a + (5 - 1)d }}  \\

 \\  \:  \:  \: \: \: \: \: \: \:  { \huge{.}} \:  \: { \bold{Fifth \:  \:  term( T_{4}) = a  + 4d  = 13  +4 ( - 12) }}  \\

 \\  \:  \:  \: \: \: \: \: \: \:  { \huge{.}} \:  \: { \bold{Fifth \:  \:  term( T_{5}) =  - 35 }}  \\

Similar questions